New method for the simultaneous determination of diffusion and adsorption of dyes in silica hydrogels - Perullini, Ana Mercedes (2014)
The fine tuning of porosity in sol gel based devices makes possible the design of novel applications in which the transport of molecules through the oxide gel plays a crucial role. In this work we develop a new method for the simultaneous analysis of diffusion and adsorption of small diffusing probes, as anionic and cationic dyes, through silica mesoporous hydrogels synthesized by sol–gel. The novelty of the work resides in the simplicity of acquisition of the experimental data (by means of a desk scanner) and further mathematical modeling, which is in line with high throughput screening procedures, enabling rapid and simultaneous determination of relevant diffusion and adsorption parameters. Net mass transport and adsorption properties of the silica based hydrogels were contrasted to dye adsorption isotherms and textural characterization of the wet gels by SAXS, as well as that of the corresponding aerogels determined by Field Emission Scanning Electron Microscopy (FESEM) and N2 adsorption. Thus, the validation of the results with well-established characterization methods demonstrates that our approach is robust enough to give reliable physicochemical information on these systems.